A study of the social space preferred by selected Filipino male adolescents - Concepcion, Alma C.
ABSTRACT This study, using a multi-method approach, aimed to determine the preferences of selected male adolescents in choosing social spaces they frequent. More specifically, the study identified the social spaces that selected Filipino male adolescents frequent, the reasons behind their preferences, the characters in design and the social interactions that attract the adolescent there. The study is significant because it added to the body of literature in culture, and in the Philippine interior design. The research may facilitate interior designers, students, and parents to better address the needs of Filipino male adolescents by providing them spaces that are supportive, which addresses the adolescents? need for individuation and social integration (Abassi, 2009). The study employed both qualitative and quantitative approach. Random sampling method was utilized in selecting twenty (20) Filipino male adolescents. Criteria of choice were based on accessibility and availability. Random selection was based on equal chances of choice. The results of the study indicate that both the physical, and social attributes of space are infused in the preferences of the male adolescents? interaction spaces. Bernaldez (1987) concurs that adolescents can perceive their spaces based on its degree of prospect, refuge and hazard. Design, lighting, comfort and temperature have a direct link to the preferred social space. Neutral colors, well-lit, and cool spaces with pleasant recall smells of home and family are shared facets of their preferred social spaces. Spaces frequented by friends, popularity and within their affordable budgets add to the preferences of social spaces. Significantly, the selected male adolescents placed optimum preference ratings to social spaces that were still family centered.